Examining the impact of multilevel upper airway surgery on the obstructive sleep apnoea endotypes and their utility in predicting surgical outcomes. Issue 10 (21st May 2022) - Wong, Ai‐Ming; Landry, Shane A.; Joosten, Simon A.; Thomson, Luke D. J.; Turton, Anthony; Stonehouse, Jeremy; Mansfield, Darren R.; Burgess, Glen; Hays, Andrew; Sands, Scott A.; Andara, Christopher; Beatty, Caroline J.; et al.
Abstract: Background and objective: Upper airway surgery for obstructive sleep apnoea (OSA) is an alternative treatment for patients who are intolerant of continuous positive airway pressure (CPAP). However, upper airway surgery has variable treatment efficacy with no reliable predictors of response. While we now know that there are several endotypes contributing to OSA (i.e., upper airway collapsibility, airway muscle response/compensation, respiratory arousal threshold and loop gain), no study to date has examined: (i) how upper airway surgery affects all four OSA endotypes, (ii) whether knowledge of baseline OSA endotypes predicts response to surgery and (iii) whether there are any differences when OSA endotypes are measured using the CPAP dial‐down or clinical polysomnographic (PSG) methods. Methods: We prospectively studied 23 OSA patients before and ≥3 months after multilevel upper airway surgery. Participants underwent clinical and research PSG to measure OSA severity (apnoea–hypopnoea index [AHI]) and endotypes (measured in supine non‐rapid eye movement [NREM]). Values are presented as mean ± SD or median (interquartile range). Results: Surgery reduced the AHITotal (38.7 [23.4 to 79.2] vs. 22.0 [13.3 to 53.5] events/h; p  = 0.009). There were no significant changes in OSA endotypes, however, large but variable improvements in collapsibility were observed (CPAP dial‐down method: ∆1.9 ± 4.9 L/min, p  = 0.09, n  = 21; PSG method: ∆3.4 [−2.8 to 49.0]% V eupnoea, p  = 0.06, n  = 20). Improvement in collapsibility strongly correlated with improvement in AHI (%∆AHISupineNREM vs. ∆collapsibility: p  < 0.005; R 2  = 0.46–0.48). None of the baseline OSA endotypes predicted response to surgery. Conclusion: Surgery unpredictably alters upper airway collapsibility but does not alter the non‐anatomical endotypes. There are no baseline predictors of response to surgery. Abstract : This is the first study to measure how upper airway surgery affects all four obstructive sleep apnoea (OSA) endotypes using both the continuous positive airway pressure dial‐down and clinical polysomnographic methods. Using either method, surgery unpredictably altered the upper airway anatomy/collapsibility and did not alter the non‐anatomical endotypes. None of the baseline OSA endotypes were able to predict the response to surgery. See related Editorial